Harvester Butterfly, Feniseca tarquinius (Fabricius) (Insecta: Lepidoptera: Lycaenidae: Melitinae) - Donald W. Hall; Marc Minno; Jerry F. Butler (EDIS, 2007)
EENY-404, a 4-page illustrated fact sheet by Donald W. Hall, Marc Minno, and Jerry F. Butler, is part of the Featured Creatures collection. It describes this small uncommon harvester butterfly whose larvae are carnivorous caterpillars, their distribution, description, life cycle and biology, and hosts. Includes selected references. Published by the UF Department of Entomology and Nematology, April 2007.